The Effect of Profitability, Leverage, and Firm Size on Corporate Social Responsibility Disclosure (E-Jurnal Akuntansi, 2026)
Corporate social responsibility (CSR) disclosure has become a regulatory obligation for public companies to report their social and environmental performance. Nevertheless, the level of CSR disclosure among manufacturing companies in Indonesia remains relatively low. This research aims to obtain evidence on how factors such as firm size, profitability, and leverage affect CSR disclosure. Utilizing multiple linear regression analysis, a total of 511 observations were gathered from manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The results indicate that CSR disclosure is positively influenced by profitability and firm size, whereas leverage has no effect on CSR disclosure. This study contributes to the application of stakeholder theory and provides practical insights for relevant parties, particularly companies and their stakeholders.
Keywords: Corporate Social Responsibility Disclosure; Profitability; Leverage; Firm Size